\(x\left(-3\right)+x-3=0\)

2,\(5x\left(x-2\r...">

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 7 2017

a,\(-3x+x-3=0\)

\(\Rightarrow-2x=3\Rightarrow x=-\dfrac{3}{2}\)

b,\(5x\left(x-2\right)-x+2=0\)

\(\Rightarrow\left(x-2\right)\left(5x-1\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x-2=0\\5x-1=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{1}{5}\end{matrix}\right.\)

Chúc bạn học tốt!!!

25 tháng 7 2017

đề sai nha : , x(x−3)+x−3=0

NV
26 tháng 2 2020

1. \(x^2\left(x+1\right)+x+1=0\)

\(\Leftrightarrow\left(x+1\right)\left(x^2+1\right)=0\)

\(\Leftrightarrow x+1=0\Rightarrow x=-1\)

2. \(\left(x-2\right)\left(6x+2\right)+\left(x-2\right)^2=0\)

\(\Leftrightarrow\left(x-2\right)\left(6x+2+x-2\right)=0\)

\(\Leftrightarrow\left(x-2\right).7x=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x-2=0\\7x=0\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x=2\\x=0\end{matrix}\right.\)

NV
26 tháng 2 2020

3.

\(x^2-5x+6=0\)

\(\Leftrightarrow x^2-2x-3x+6=0\)

\(\Leftrightarrow x\left(x-2\right)-3\left(x-2\right)=0\)

\(\Leftrightarrow\left(x-3\right)\left(x-2\right)=0\Rightarrow\left[{}\begin{matrix}x=2\\x=3\end{matrix}\right.\)

4.

\(x^2-x-6=0\)

\(\Leftrightarrow x^2+2x-3x-6=0\)

\(\Leftrightarrow x\left(x+2\right)-3\left(x+2\right)=0\)

\(\Leftrightarrow\left(x-3\right)\left(x+2\right)=0\Rightarrow\left[{}\begin{matrix}x=3\\x=-2\end{matrix}\right.\)

11 tháng 1 2018

a ) \(\left(5x+7\right)\left(x-7\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{7}{5}\\x=7\end{matrix}\right.\)

b ) \(\left(x^2-1\right)\left(x+3\right)=0\)

\(\Leftrightarrow\left(x-1\right)\left(x+1\right)\left(x+3\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=-1\\x=-3\end{matrix}\right.\)

c )\(x^2-x-6=0\)

\(\Leftrightarrow x^2-3x+2x-6=0\)

\(\Leftrightarrow\left(x+2\right)\left(x-3\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-2\\x=3\end{matrix}\right.\)

d ) \(x^2+x-12=0\)

\(\Leftrightarrow x^2-4x+3x-12\)

\(\Leftrightarrow\left(x+3\right)\left(x-4\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-3\\x=4\end{matrix}\right.\)

e ) \(15\left(x+9\right)\left(x-3\right)\left(x+21\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-9\\x=3\\x=-21\end{matrix}\right.\)

g ) \(\left(x^2+1\right)\left(x^2+4x+4\right)=0\)

\(\Leftrightarrow\left(x^2+1\right)\left(x+2\right)^2=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x^2=-1\left(loại\right)\\x=-2\end{matrix}\right.\)

i ) \(x^4+2x^3-2x^2+2x-3=0\)

\(\Leftrightarrow x^4+3x^3-x^3-3x^2+x^2+3x-x-3=0\)

\(\Leftrightarrow x^3\left(x+3\right)-x^2\left(x+3\right)+x\left(x+3\right)-\left(x+3\right)=0\)

\(\Leftrightarrow\left(x^3-x^2+x-1\right)\left(x+3\right)=0\)

\(\Leftrightarrow\left(x^2+1\right)\left(x-1\right)\left(x+3\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x^2=-1\left(loại\right)\\x=1\\x=-3\end{matrix}\right.\)

h) \(x^2+5x+6=0\)

\(\Leftrightarrow x^2+3x+2x+6=0\)

\(\Leftrightarrow\left(x+2\right)\left(x+3\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-2\\x=-3\end{matrix}\right.\)

7 tháng 6 2017

n) \(\left|3-x\right|+x^2-x\left(x+4\right)=0\)

\(\Rightarrow\left|3-x\right|+x^2-x^2-4x=0\)

\(\Leftrightarrow\left[{}\begin{matrix}3-x-4x=0\left(đk:3-x\ge0\right)\\-\left(3-x\right)-4x=0\left(đk:3-x< 0\right)\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{3}{5}\left(đk:x\le3\right)\\x=-1\left(đk:x>3\right)\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{3}{5}\\x\in\varnothing\end{matrix}\right.\)

Vậy \(x=\dfrac{3}{5}\)

m) \(\left(x-1\right)^2+\left|x+21\right|-x^2-13=0\)

\(\Rightarrow x^2-2x+1+\left|x+21\right|-x^2-13=0\)

\(\Leftrightarrow-2x-12+\left|x+21\right|=0\)

\(\Leftrightarrow\left[{}\begin{matrix}-2x-12+x+21=0\left(đk:x+21\ge0\right)\\-2x-12-\left(x+21\right)=0\left(đk:x+21< 0\right)\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=9\left(đk:x\ge-21\right)\\x=-11\left(đk:x< -21\right)\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=9\\x\in\varnothing\end{matrix}\right.\)

Vậy \(x=9\)

7 tháng 6 2017

e) \(\left|5x\right|=3x-2\)

\(\Rightarrow5\cdot\left|x\right|=3x-2\)

\(\Leftrightarrow5\cdot\left|x\right|-3x=-2\)

\(\Leftrightarrow\left[{}\begin{matrix}5x-3x=-2\left(đk:x\ge0\right)\\5\cdot\left(-x\right)-3x=-2\left(đk:x< 0\right)\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-1\left(đk:x\ge0\right)\\x=\dfrac{1}{4}\left(đk:x< 0\right)\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x\in\varnothing\\x\in\varnothing\end{matrix}\right.\)

Vậy \(x\in\varnothing\)

g) \(\left|-2,5x\right|=x-12\)

\(\Rightarrow2,5\cdot\left|x\right|=x-12\)

\(\Leftrightarrow2x5\cdot\left|x\right|-x=-12\)

\(\Leftrightarrow\left[{}\begin{matrix}2,5x-x=-12\left(đk:x\ge0\right)\\2,5\cdot\left(-x\right)-x=-12\left(đk:x< 0\right)\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-8\left(đk:x\ge0\right)\\x=\dfrac{24}{7}\left(đk:x< 0\right)\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x\in\varnothing\\x\in\varnothing\end{matrix}\right.\)

Vậy \(x\in\varnothing\)

AH
Akai Haruma
Giáo viên
13 tháng 8 2018

a)

\(3x^2-5x=0\Leftrightarrow x(3x-5)=0\)

\(\Rightarrow \left[\begin{matrix} x=0\\ 3x-5=0\rightarrow x=\frac{5}{3}\end{matrix}\right.\)

b)

\(x^3-0,36x=0\Leftrightarrow x(x^2-0,36)=0\)

\(\Leftrightarrow x(x-0,6)(x+0,6)=0\)

\(\Rightarrow \left[\begin{matrix} x=0\\ x-0,6=0\\ x+0,6=0\end{matrix}\right.\Rightarrow \left[\begin{matrix} x=0\\ x=0,6\\ x=-0,6\end{matrix}\right.\)

c)

\((5x+2)^2-(3x-1)^2=0\)

\(\Leftrightarrow (5x+2-3x+1)(5x+2+3x-1)=0\)

\(\Leftrightarrow (2x+3)(8x+1)=0\)

\(\Rightarrow \left[\begin{matrix} 2x+3=0\\ 8x+1=0\end{matrix}\right.\Rightarrow \left[\begin{matrix} x=\frac{-3}{2}\\ x=\frac{-1}{8}\end{matrix}\right.\)

AH
Akai Haruma
Giáo viên
13 tháng 8 2018

d)

\(x^2-10x=-25\)

\(\Leftrightarrow x^2-10x+25=0\)

\(\Leftrightarrow x^2-2.5x+5^2=0\Leftrightarrow (x-5)^2=0\)

\(\Rightarrow x=5\)

e)

\(3(x+5)-x^2-5x=0\)

\(\Leftrightarrow 3(x+5)-x(x+5)=0\)

\(\Leftrightarrow (3-x)(x+5)=0\)

\(\Rightarrow \left[\begin{matrix} 3-x=0\rightarrow x=3\\ x+5=0\rightarrow x=-5\end{matrix}\right.\)

f)

\((x-1)^2-2(x-1)(3x+2)+(3x+2)^2=0\)

\(\Leftrightarrow [(x-1)-(3x+2)]^2=0\)

\(\Leftrightarrow (-2x-3)^2=0\Rightarrow -2x-3=0\Rightarrow x=\frac{-3}{2}\)

31 tháng 7 2018

1,x^2-(x+1)(x-1)=0
x^2-x^2+1+0
1=0(vô lý)
2,5x^3+3x^2+3x+1=4x^2
x^3+3x^2+3x+1=0
(x+1)=0
x=-1
3,x^3+x^2=0
x^2(x+1)=0
x=0 or x=-1
4,2x^3-12x^2+18x=0
x^3-6x^2+9x=0
x(x^2-6x+9)=0
x(x-3)^2=0
x=0 or x=3
5,5x^2-4(x^2-2x+1)+20=0
5x^2-4x^2+8x-4+20=0
x^2+8x+16=0
(x+4)^2=0
x=-4
6,5x(x-3)+7x-21=0
5x(x-3)+7(x-3)=0
(5x+7)(x-3)=0
5x-7=0 or x-3=0
x=7/5 or x=3
7,2x^3-50x=0
2x(x^2-25)=0
2x(x-5)(x+5)=0
x=0 or x=5 or x=-5
8,(4x-1)^2-9(x+3)^2=0
(4x-1)^2-3^2*(x+3)^2=0
(4x-1)^2-(3x+9)^2=0
(4x-1-3x-9)(4x-1+3x+9)=0
(x-10)(7x+8)=0
x=10 or x=-8/7
9,3(x-2)^2-x+2=0
3*(x-2)*(x-2)-(x-2)=0
(3x-6)(x-2)-(x-2)=0
(x-2)(3x-6-1)=0
(x-2)(3x-7)=0
x=2 or x=7/3
10,9x^2+6x-8=0
9x^2+12x-6x-8=0
3x(3x-2)+4(3x-2)=0
(3x+4)(3x-2)=0
3x+4=0 or 3x-2=0
x=-4/3 or x=2/3

25 tháng 6 2019

Tìm x,biết:

a/ x + 5x2 =0

⇔x ( 1 + 5x ) = 0

\(\Leftrightarrow\) x = 0 hoặc 1 + 5x = 0

1) x = 0

2) 1+ 5x = 0 \(\Leftrightarrow\) x = \(\frac{-1}{5}\)

Vậy: S = \(\left\{0;\frac{-1}{5}\right\}\)

b/x+1=(x+1)2

\(\Leftrightarrow\) (x+1) - (x+1)2 = 0

\(\Leftrightarrow\) ( x+ 1)(1-x-1) = 0

\(\Leftrightarrow\) (x+1).(-x) = 0

\(\Leftrightarrow\) x+1 = 0 hoặc x = 0

\(\Leftrightarrow\) x= -1 ; 0

Vậy: S=\(\left\{-1;0\right\}\)

c/ x3+x=0

\(\Leftrightarrow\) x(x2 + 1) = 0

\(\Leftrightarrow\) x = 0 hoặc x2 + 1 = 0

Ta có : x2 + 1 \(\ge\) 0 vs mọi x

Vậy: S = \(\left\{0\right\}\)


d/5x(x2)(2x)=0

\(\Leftrightarrow\) 5x(x-2) + (x - 2) = 0

\(\Leftrightarrow\) (x - 2)(5x+1) = 0

\(\Leftrightarrow\) x - 2 = 0 hoặc 5x+ 1 = 0

\(\Leftrightarrow\) x = 2 hoặc x = \(\frac{-1}{5}\)

Vậy: S = \(\left\{\frac{-1}{5};2\right\}\)

g/ x(x4)+(x4)2=0

⇔ (x - 4)( x+x-4) = 0

\(\Leftrightarrow\) x - 4 = 0 hoặc 2x-4=0

\(\Leftrightarrow\) x = 4 hoặc x = 2

Vậy: S= \(\left\{2;4\right\}\)

h/ x23x=0

⇔x (x-3) = 0

\(\Leftrightarrow\) x = 0 hoặc x = 3

Vậy: S = \(\left\{0;3\right\}\)

Vậy: S= \(\left\{0;3\right\}\)
i/4x(x+1)=8(x+1)

4x(x+1)-8(x+1) = 0

\(\Leftrightarrow\) 4(x+1) (x - 2) = 0

\(\Leftrightarrow\) x+1 = 0 hoặc x - 2 = 0

\(\Leftrightarrow\) x= -1 hoặc x = 2

Vậy: S=\(\left\{-1;2\right\}\)

14 tháng 5 2019

casio fx 570vn

a: \(\Leftrightarrow x^2\left(x^2+x-12\right)=0\)

\(\Leftrightarrow x^2\left(x+4\right)\left(x-3\right)=0\)

hay \(x\in\left\{0;-4;3\right\}\)

d: \(\left(x^2+5x\right)^2-2\left(x^2+5x\right)-24=0\)

\(\Leftrightarrow\left(x^2+5x-6\right)\left(x^2+5x+4\right)=0\)

\(\Leftrightarrow\left(x+6\right)\left(x-1\right)\left(x+1\right)\left(x+4\right)=0\)

hay \(x\in\left\{-6;1;-1;-4\right\}\)

f: \(x\left(x+1\right)\left(x-1\right)\left(x+2\right)=24\)

\(\Leftrightarrow\left(x^2+x\right)\left(x^2+x-2\right)=24\)

\(\Leftrightarrow\left(x^2+x\right)^2-2\left(x^2+x\right)-24=0\)

\(\Leftrightarrow x^2+x-6=0\)

\(\Leftrightarrow\left(x+3\right)\left(x-2\right)=0\)

hay \(x\in\left\{-3;2\right\}\)